Current evidence on the impact of the COVID-19 pandemic on paediatric endocrine conditions - Gnocchi, Margherita; D’Alvano, Tiziana; Lattanzi, Claudia; Messina, Giulia; Petraroli, Maddalena; Patianna, Viviana D.; Esposito, Susanna; Street, Maria E. (Frontiers in Endocrinology, 2022)
Severe acute respiratory coronavirus 2 (SARS-CoV-2) interacts with the host cells through its spike protein by binding to the membrane enzyme angiotensin-converting enzyme 2 (ACE2) and it can have a direct effect on endocrine function as ACE2 is expressed in many glands and organs with endocrine function. Furthermore, several endocrine conditions have features that might increase the risk of SARS-CoV-2 infection and the severity and course of the infection, as obesity for the underlying chronic increased inflammatory status and metabolic derangement, and for the possible changes in thyroid function. Vitamin D has immunomodulatory effects, and its deficiency has negative effects. Adrenal insufficiency and excess glucocorticoids affect immune conditions also besides metabolism. This review aims to analyze the rationale for the fear of direct effects of SARS-Cov-2 on endocrinological disorders, to study the influence of pre-existing endocrine disorders on the course of the infection, and the actual data in childhood. Currently, data concerning endocrine function during the pandemic are scarce in childhood and for many aspects definite conclusions cannot be drawn, however, data on properly managed patients with adrenal insufficiency at present are re-assuring. Too little attention has been paid to thyroid function and further studies may be helpful. The available data support a need for adequate vitamin D supplementation, caution in obese patients, monitoring of thyroid function in hospitalized patients, and confirm the need for an awareness campaign for the increased frequency of precocious puberty, rapidly progressive puberty and precocious menarche. The changes in lifestyle, the increased incidence of overweight and the change in the timing of puberty lead also to hypothesize that there might be an increase in ovarian dysfunction, as for example polycystic ovarian disease, and metabolic derangements in the next years, and in the future we might be facing fertility problems. This prompts to be cautious and maintain further surveillance.